2005
DOI: 10.1097/01.brs.0000162278.68000.91
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Mechanical Spinal Hemiepiphysiodesis Modifies Spine Growth

Abstract: Spinal hemiepiphysiodesis using an anatomically based implant and minimally invasive procedures repeatedly induced spine curvature in a normal porcine model. These techniques may slow, and perhaps even correct, early progressive spine deformity without long rod instrumentation or fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 26 publications
1
32
0
1
Order By: Relevance
“…Studies such as those by Beguiristáin et al and Zhang and Sucato [3,5] emphasised NCC asymmetry as a cause of structured scoliosis. However, other studies demonstrated the effects of EP on vertebral wedging which in turn develop scoliotic deformity [1,2]. The results from these studies prompted us to analyse the effectiveness of physiodesis of EP and/or NCC by direct electrocoagulation decreasing the possibilities of surgical complications due to the potential extrusion of the implants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies such as those by Beguiristáin et al and Zhang and Sucato [3,5] emphasised NCC asymmetry as a cause of structured scoliosis. However, other studies demonstrated the effects of EP on vertebral wedging which in turn develop scoliotic deformity [1,2]. The results from these studies prompted us to analyse the effectiveness of physiodesis of EP and/or NCC by direct electrocoagulation decreasing the possibilities of surgical complications due to the potential extrusion of the implants.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wall et al [1] implanted staples using thoracoscopy in seven mediothoracic vertebrae in immature pigs. Each assembly covered the intervertebral disc and the superior physeal cartilage of the lower vertebra, as well as the inferior physeal cartilage of the upper vertebra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic spinal hemiepiphysiodesis, via custom spine staples, was performed in pig vertebrae and was shown to modify the spinal growth effectively. No staple back-out was reported [42]. Asymmetrical static loading rat tail was shown to create vertebral wedging [29].…”
Section: Experimental Research On Spinal Growth Modulationmentioning
confidence: 99%
“…These minimally invasive approaches maintain a certain spinal flexibility depending on the rigidity of the implant. Wall et al [18] introduced a rigid 2-prong vertebral staple that fixes two adjacent vertebral bodies, while slowing down growth on one side of the spine. These were tested on a pig model and showed the ability to induce significant spinal curvature (reverse problem).…”
Section: Introductionmentioning
confidence: 99%